The problem of using English reading strategies perceived by Thai EFL students - Atichat Rungswang; Krishna Kosashunhanan (My University, 2021)
It is recognized that reading ability is essential for Thai EFL students and English reading is perceived as a difficult task among them. To understand the difficulty experienced by the students while reading English text, this study hence aimed at investigating problems of using English reading strategies perceived by Thai EFL students as well as providing suggested reading instructions for Thai lecturers to cope with the emerging problems. This study employed a mixed-method design. The participants of the study were 412 Thai EFL students who, in this study, were also considered as Gen Z students at a large-size university in Bangkok, Thailand. The participants were asked to complete an online questionnaire on 4-point Likert’s scale, which was adapted from Aebersold and Field (1997). Moreover, 10 students were recruited for two focus group interviews. The results revealed that Thai EFL students experience difficulties in using English reading strategies when they have to skip unknown words during the first reading (mean = 2.67, SD = 1.01) followed by varying reading speed rates according to the type of the reading passage (mean = 2.66, SD = 0.97), and guessing the meanings of unknown words by using the context clues (mean = 2.59, SD = 0.92) respectively. Based on both quantitative and qualitative results and personality traits of Thai Gen Z, suggested reading instructions including guided reading, improving student’s vocabulary knowledge and reading comprehension, technology-blended classroom and critical reading were purposed.
Keywords: Generational Differences and Trends